Evaluation of Management Functions at Pondok Pesantren Tafidz Putri Darul Quran Mojokerto - Adawiyah, Indriyati; Riyanto, Yatim; Karwanto, Karwanto; Roesminingsih, Erny; Yahya, Yuniar Indra (Studies in Philosophy of Science and Education, 2024)
The four management functions in an organization that must be implemented in order to experience significant progress towards the development of another agency include planning, organizing, directing, and controlling. Therefore, Islamic boarding schools must have good management in achieving an educational vision and mission according to the needs of the times, namely al-muhafadzah 'ala alqadim al-shalih wal-akhdzu bi al-jadid al-ashlah. This article aims to analyze the four management functions that have been implemented by the Tahfidz Putri Darul Quran Mojokerto Islamic Boarding School. The results of the research show that the steps of the management function can be used as a basis for compiling, implementing, and disseminating Islamic boarding school goals in a better direction through the implementation of a global education system. Global education as a systematic effort to shape students' insight revolves around the Tahfidz Putri Darul Qur`an Islamic Boarding School curriculum in Mojokerto.